Performance, acceptability, and validation of a phone application bowel diary. Issue 8 (22nd September 2020) - Zyczynski, Halina M.; Richter, Holly E.; Sung, Vivian W.; Arya, Lily A.; Lukacz, Emily S.; Visco, Anthony G.; Rahn, David. D.; Carper, Benjamin; Mazloomdoost, Donna; Gantz, Marie G.; ,
Abstract: Aims: To assess performance, acceptability, external validity, and reliability of a phone application electronic bowel diary ( PFDN Bowel eDiary). Methods: Women reporting refractory accidental bowel leakage (ABL) were enrolled in a randomized, crossover trial evaluating paper versus eDiary documentation of bowel movements (BM) and fecal incontinence episodes (FIE). Events were characterized by the presence or absence of urgency and Bristol stool scale consistency. The eDiary entries were date/time stamped and prompted by twice‐daily phone notifications. Women were randomized to complete up to three consecutive 14‐day diaries in two sequences. Diary events were compared between formats using the Pearson correlation. System usability scale (SUS) assessed eDiary usability. The eDiary test‐retest reliability was assessed with intraclass correlations (ICCs). Results: Paired diary data were available from 60/69 (87%) women 63.8 ± 9.8 years old with mean 13.2 BM per week and 6.5 FIE per week (nearly half with urgency). Among those providing diaries, adherence did not differ by paper or eDiary (93.3% vs. 95.0%). Notifications prompted 29.6% of eDiary entries, improving adherence from 70% to 95%. Paper and eDiaries were moderate to‐strongly correlated for BMs per week ( r  = .61), urgency BMs per week ( r  = .76), FIE per week ( r  = .66), urgency FIE per week ( r  = .72). Test‐retest reliability was good (ICC = .81 BMs per week,  .79 urgency BMs per week,  .74 FIE per week, and .62 urgency FIE per week). The mean SUS score was high, 82.3 ± 17.5 (range, 0–100) with 91.4% rating it easy to use, and 75.9% preferring the eDiary over paper. Conclusion: The PFDN Bowel eDiary correlated well with paper diary was considered easy to use, preferred to paper diaries, had high rates of confirmed real‐time diary completion that obviated staff data entry.